THE IMPORTANCE OF MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE: CASE STUDY: ISLAMIC HIGH SCHOOL ITTIFAQIAH INDRALAYA - Pebrikarlepi, Erik; Firdaus , Febrian Zainiyatul (LP2M IAI Al-Khairat Pamekasan, 2022)
Motivation is one of the key factors of success and also failure in learning language and it plays a significant role in the process of learning a language. However most of students are lack of motivation and lose their willingness in learning a foreign language. Language teachers cannot effectively teach a language if learners do not have good motivation. That is why teacher should pay more attention to communicative learning that can stimulate students’ motivation. This paper tries to discuss the EFL learners’ motivation in learning a foreign language that includes its definitions from different views, types, and the importance of motivation in learning English as foreign language. Finally it concludes that motivation has an influential and crucial role in all aspects of language learning.